The spiraling story of Tyleropappus and a new name for Calea (Asteraceae: Neurolaeneae) from Venezuela - Bueno, Vinicius R.; Gostel, Morgan R.; Heiden, Gustavo (Phytotaxa, 2023)
Tyleropappus was described in 1931 by Greenman and is characterized by its spiral, alternate leaves and epaleaceous receptacle. Throughout its taxonomic history, the genus was placed into the tribes Helenieae and Neurolaeneae, often treated as the sister genus of Geissopappus, which is currently a synonym of Calea. Later, Tyleropappus was synonymized with Calea; however, when its synonymization was proposed, the sole species in the genus, T. dichotomus, had not been synonymized under a previously described species nor properly transferred to Calea. Ongoing taxonomic studies in Neurolaeneae have provided opportunities to clarify the challenging taxonomic history of this monotypic genus. We confirm the synonymy of Tyleropappus in Calea; however, we recognize T. dichotomus as a distinct species that should be accepted in Calea. Nonetheless, the name C. dichotoma already exists, and is a synonym of C. ternifolia. Therefore, we propose the new name C. spiralis to accommodate this species, which is morphologically similar to C. linearifolia. The former can be distinguished from the latter by the spiral, alternate (vs. decussate) arrangement of leaves, receptacle epaleaceous (vs. oligopaleaceous) and cypselae hirsute (vs. glabrous). We also provide a detailed description of the species, the first map of its geographic occurrence, an illustration with diagnostic characters, and the first taxonomic key for the Nana clade of Calea.